Externalist Individualism: A New Ontological Approach of Diseases - Hatef, Mohammad (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The understanding of disease in the dominant biomedical model involves two components, internalism and individualism, which jointly give rise to an ontological approach towards patients that can be referred to as atomism. I argue against such an approach in philosophy of medicine. I focus on internalism, showing that the inevitable presence of the notions of biological function and statistical normality in the biomedical model renders internalism about diseases untenable. Additionally, I argue that the new externalist individualism offers an alternative ontological approach that escapes the challenges to which the atomistic approach is exposed regarding both the concept of disease and medical practice. Subsequently, I focus on an implication of this new approach which relates to the idea of diseases as natural kinds, demonstrating that it proposes a concept of diseases as natural kinds that is conceptually consistent.